Recording characteristics of electrical impedance-electromyography needle electrodes. (22nd May 2018) - Kwon, H; Di Cristina, J F; Rutkove, S B; Sanchez, B
Abstract: Objective : Needle EMG remains the standard clinical test for neuromuscular disease (NMD) assessment, but it only characterizes myofiber membrane depolarization. On the other hand, electrical impedance provides non-electrically active structural and compositional data of tissues. Here, we designed a prototype of needle electrode integrating electrical impedance and EMG measurement capabilities, the so-called I-EMG needle electrode. Approach : We use finite element method models to study the impedance recording characteristics of I-EMG needle electrodes. The simulated electrical and mechanical design specifications are then manufactured to create a prototype of an I-EMG needle electrode. We pilot these new needle electrodes by conducting in vivo impedance measurements with muscle at rest on healthy wild-type (wt, n = 5) and muscular dystrophy (mdx, n = 5) mice. Comparisons between wt and mdx mice are performed using Mann–Whitney test, two-tailed, p < 0.05. The electrical characterization of the EMG electrode in the developed I-EMG needles was performed in vitro on saline solution and through EMG detection in wt animal at rest and during voluntary contractions. Results : Muscle impedance demonstrate good repeatability ( p < 0.05 and p < 0.005 for resistance and reactance at 50 kHz, respectively) and agreement between different I-EMG needles. Impedance data allows us to discriminate between mdx and wt muscle ( p < 0.05 and p < 0.005 for resistance and reactance at 10 kHz, respectively). EMG broadband noise power and peak amplitude using the I-EMG needle were similar to that of a commercial monopolar EMG needle. EMG recordings using the I-EMG needle measured electrical activity similar to a standard monopolar needle with muscle at rest and during voluntary contraction. Significance : Needle I-EMG technology may offer the opportunity to enhance the diagnostic capability and quantification of NMD beyond that possible with either impedance or EMG techniques separately. Ultimately, needle I-EMG could serve as a new bedside tool to assess NMD without increasing the complexity or duration of the EMG test.